Quantifying Loss-Averse Tax Manipulation - Rees-Jones, Alex (Review of Economic Studies, 2018)
This article presents evidence that loss aversion affects taxpayers as they file their annual tax returns, and presents a framework for estimating the policy impact of this psychological phenomenon. In my theoretical framework, taxpayers manipulate the money paid to the tax authority through avoidance and evasion activities. When taxpayers face the prospect of owing the tax authority money on tax day, loss aversion generates the perception of a greater marginal utility of tax reduction and therefore motivates greater pursuit of tax reduction activities. Applying a bunching-based identification strategy to U.S. tax return data, I estimate that taxpayers facing a payment on tax day reduce their tax liability by $34 more than taxpayers owed a refund.